помогите пожалуйста решить уравнение: (х^2 - 6х)^2 + 14(х-3)^2 = 81

0 голосов
43 просмотров

помогите пожалуйста решить уравнение:

(х^2 - 6х)^2 + 14(х-3)^2 = 81


Алгебра (57.1k баллов) | 43 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

(х^2 - 6х)^2+14(х^2 - 6х+9)=81

(х^2 - 6х)^2+14(х^2 - 6х)+126=81

(х^2 - 6х)^2+14(х^2 - 6х)+45=0

Заменим х^2 - 6х=у

y^2+14y+45=0

D=196-180=16

y1= -5. y= -9

вернемся к замене

1) х^2 - 6х=-5

х^2 - 6х+5=0

D=36-20=16

x1=5. x2=1

2) х^2 - 6х=-9

х^2 - 6х+9=0

D=36-36=0

x3=3

Ответ 1, 3, 5

(271k баллов)